KESIAPAN KOPERASI INDONESIA MENDUKUNG RENSTRA KEMENTERIAN KOPERASI DAN UKM REPUBLIK INDONESIA - putong, iskandar (Jurnal Manajemen Update, 2012)
Abstract Analysis of Indonesian Cooperatives readiness to support the ministry RENSTRA RI , using the entire sample of cooperatives in Indonesia 's 33 provinces in the period 2011 to 2012. The purpose of the analysis is to determine whether the cooperatives in Indonesia is ready or not to support the ministry RENSTRA RI based business variables(Equity,Foreign Equity, Business Volume and SHU ) and non-business (Number of Active Cooperative, Member Number, Number of Employees, Total Manager and Total RAT). Proxy analysis is to determine whether the variables are variables that affect the theoretical and empirical experience convergence or not. Data analysis using econometric models with cointegration test and Error Correction Mechanism technique with a confidence level between 90 % to 99 %. The results of the analysis showed that all the variables are theoretically and empirically effect, statistically converge with some of them experiencing error correction in the short term. Based on the analysis it can be concluded that the cooperative in Indonesia supports the Strategic Plan 2010 - 2014 and 2014 2018 Keywords: Cooperative, Strategic Plan, Business and Non-Business Variables, Convergence, Cointegration